Dependence-induced increases in ethanol self-administration in mice are blocked by the CRF(1) receptor antagonist antalarmin and by CRF(1) receptor knockout - Chu, Kathleen (2007)
Models of dependence-induced increases in ethanol self-administration will be critical in increasing our understanding of the processes of addiction and relapse, underlying mechanisms, and potential therapeutics. One system that has received considerable attention recently is the CRF(1) system that may mediate the link between anxiety states and relapse drinking. C57BL/6J mice were trained to lever press for ethanol, were made dependent and then were allowed to self-administer ethanol following a period of abstinence. The effect of the CRF(1) antagonist, antalarmin, was examined on this abstinence-induced self-administration in a separate group of mice. Finally, dependence-induced changes in ethanol self-administration were examined in CRF(1) knockout and wild type mice. The results indicated that ethanol self-administration was increased following the induction of dependence, but only after a period of abstinence. This increase in ethanol self-administration was blocked by antalarmin. Furthermore, CRF(1) knockout mice did not display this increased ethanol self-administration following dependence and abstinence. These studies, using both a pharmacological and genetic approach, support a critical role for the CRF(1) system in ethanol self-administration following dependence. In addition, a model is presented that may be useful for studies examining underlying mechanisms of the ethanol addiction process as well as for testing potential therapeutics.